Fredholm Weighted Composition Operators on Weighted Banach Spaces of Analytic Functions of Type H∞ - M. Carmen Gómez-Collado; David Jornet (Journal of Function Spaces)
We study Fredholm (weighted) composition operators between general weighted Banach spaces of analytic functions on the open unit disc with sup-norms.